Mesenchymal Stromal/Stem Cells in the Tumor Microenvironment and Their Role in Tumor Progression - Kargar Jahromi, Hossein; Shahabi Raberi , Venus; Abdollahi Moghadam, Samira; Poudineh, Maryam; Barghgir, Behnaz; Molaee Eshgh Abad , Maryam; Jafarinia , Morteza; Sharafi , Ensieh (Galen Medical Journal, 2022)
Mesenchymal stromal/stem cells (MSCs) are a source of stem cells that can be easily harvested and differentiated into numerous cells. Over the past few decades, these cells have been introduced as promising therapeutic candidates for different diseases. Different studies have shown the role of these cells in regenerative medicine. Tumor growth is correlated with the interactions between MSCs and tumor cells in the tumor microenvironment. The precise key role played by MSCs in the progression of tumors is under question, and the effect of MSCs on the tumor is controversial it might involve the development of tumor initiation or prevent the spread of already existing ones. In this study, we reviewed the role of MSCs in the tumor microenvironment and their influence on promoting or inhibiting tumor progression.